2018
DOI: 10.1002/smll.201702731
|View full text |Cite
|
Sign up to set email alerts
|

P‐GaSe/N‐MoS2 Vertical Heterostructures Synthesized by van der Waals Epitaxy for Photoresponse Modulation

Abstract: The important role of p-n junction in modulation of the optoelectronic properties of semiconductors is widely cognized. In this work, for the first time the synthesis of p-GaSe/n-MoS heterostructures via van der Waals expitaxial growth is reported, although a considerable lattice mismatching of ≈18% exists. According to the simulation, a significant type II p-n junction barrier located at the interface is expected to be formed, which can modulate optoelectronic properties of MoS effectively. It is intriguing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 68 publications
5
70
0
Order By: Relevance
“…In addition, Raman spectroscopy is sensitive to interlayer coupling in the heterostructures . The A 1g mode of In 2 S 3 exhibits obvious red‐shift at the heterostructure, in contrast to the E 1g mode exhibiting a weak blue‐shift, suggesting electron‐doping of In 2 S 3 at the heterostructure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Raman spectroscopy is sensitive to interlayer coupling in the heterostructures . The A 1g mode of In 2 S 3 exhibits obvious red‐shift at the heterostructure, in contrast to the E 1g mode exhibiting a weak blue‐shift, suggesting electron‐doping of In 2 S 3 at the heterostructure …”
Section: Resultsmentioning
confidence: 99%
“…[10] The A 1g mode of In 2 S 3 exhibits obvious red-shift at the heterostructure, in contrast to the E 1g mode exhibiting a weak blue-shift, suggesting electron-doping of In 2 S 3 at the heterostructure. [22] In order to reveal the interlayer electron-hole separation behavior at the In 2 S 3 /graphene/Si interface, photoluminescence (PL) measurements were performed. As shown in Figure 2a, In 2 S 3 on the SiO 2 substrate presents an obvious PL peak at 650 nm, which corresponds to a bandgap of 1.91 eV.…”
Section: Resultsmentioning
confidence: 99%
“…However, the atomically thin nature of 2D MoS 2 crystals results in an extremely inefficient light‐trapping ability, which is a fatal flaw for photodetector devices. The practical application of MoS 2 ‐based photodetectors is also hindered by severely limited photoresponse and detecting capability, slow response rate, etc. As a result, many efforts have been made to optimize the performance of atomic‐layer MoS 2 ‐based optoelectronics …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the use of hybrid photodetectors (HPs) can mitigate the disadvantages of atomically thin MoS 2 crystals. Under the synergistic effect of multimaterials, hybrid MoS 2 ‐based devices show improved response rates and responsivities . For example, the photoresponse rate of a MoS 2 ‐based device increased by almost three orders of magnitude by constructing the heterojunctions with GaSe flakes, and a greatly increased responsivity (10 6 A W −1 ) was achieved in a TiO 2 ‐encapsulated MoS 2 transistor–modified by HgTe quantum dots .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation